pengaruh DAU Dan DAK Terhadap Alokasi Belanja Modal Dengan Kebijakan Anggaran Sebagai Variabel Moderating Pada Pemerintah Daerah Kabupaten Sorong - Yekwan, Sarlota (Universitas Sam Ratulangi, 2018)
The purpose of this study was to determine whether simultaneously DAU and DAK affect the allocation of capital expenditure with the budget policy as a moderating variable at the Government of Sorong District. To find out whether partially DAU and DAK affect the allocation of capital expenditure. This research using the quantitative methode with assosiatif model. The results of the study is simultaneously DAU and DAK variables influence to capital expenditure allocation with budget policy as moderating variable to Sorong Government. Partially DAU variable positively and significantly influence to capital expenditure allocation and DAK variable have positive and significant influence to capital expenditure allocation.Keywords: DAU, DAK, Performance, capital expenditure allocation, budget policy